Analytical characteristics of developing a multiplexed bioassay using circulating cell-free tumor DNA to simultaneously detect primary and secondary (acquired) mutations in patients with advanced gastrointestinal stromal tumors - Lim, Rebecca Rui Jia (2015)
Gastrointestinal stromal tumors (GISTs) are mesenchymal malignancies characterized by a set of primary mutations mainly in KIT and PDGFRα. Secondary mutations conferring resistance to targeted therapeutic drugs also tend to arise along the course of clinical treatment. The presence of circulating tumor DNA in the blood may serve as a promising biomarker due to its biological specificity. This study aims to evaluate the analytical characteristics of developing a multiplexed bioassay that simultaneously detects primary and secondary mutations in plasma circulating cell-free DNA (ccfDNA). Patient-specific primer pairs were designed to amplify target regions along KIT and PDGFRα and tested for their functionality and specificity in multiplex PCR. Targeted multiplex PCR amplification followed by amplicon sequencing (Illumina MiSeq) of low-input tumor DNA (tDNA) dilutions and plasma ccfDNA samples were performed to evaluate the sensitivity of variant detection. Serial tDNA dilutions revealed a positive linear correlation (R-squared=0.86492) between the expected and observed variant allele frequencies observed after sequencing analysis. The sensitivity of detecting primary mutations in plasma ccfDNA was 62.5% and unknown secondary mutations were also detected. The results indicate that this assay could potentially be used as a minimally invasive clinical diagnostic tool. However, further downstream validation would be required.